Universal Archetypes in the Novel «Alkhalalalai» by the Sami Writer N. Bolshakova - Andrey A. Emashev; Viktoria B. Bakula (Publishing house "Sreda", 2022)
The literature of the Kola Sami, an indigenous small-numbered people of the Arctic, is still insufficiently researched by literary critics and is little known to the scientific community. The novel «Alkhalalalai» by Nadezhda Bolshakova, a member of the Writers' Union of Russia, is the first novel in the literature of the Kola Sami. The article is devoted to the study of the archetypal basis of the novel. The analysis of universal archetypes of the Great Mother, Virgin, Heavenly Father, Rebirth, etc. is carried out. The methodology of the research consists of works in the field of cultural studies, ethnography, anthropology and psychology; mythology and folklore; literary theory; literary studies of Sami literature. The main methodological principle in the work was the application of C.G. Jung's theory of archetypes, reinterpreted by literary criticism. To solve the research tasks, methods of theoretical analysis of works in the field of anthropology, cultural studies, mythology, folklore, literary studies were used; synthesis of the data obtained; comparative analysis. As a result of the analysis, it was found that in the text of the work, the worldview of the aborigines of the North was reflected, among other things, in the system of universal archetypes, ritual and mytho-folklore elements. Since the novel belongs to ethnic literatures, elements of the archaic worldview of ancient man are strong in it. The literary creativity of the Sami is still influenced by the myths and folklore of the Northern culture.